Characterization of a Plasmodium berghei sexual stage antigen PbPH as a new candidate for malaria transmission-blocking vaccine. Issue 1 (December 2016) - Kou, Xu; Zheng, Wenqi; Du, Feng; Liu, Fei; Wang, Meilian; Fan, Qi; Cui, Liwang; Luo, Enjie; Cao, Yaming
Abstract Background Transmission-blocking vaccines (TBVs) are a promising strategy for malaria control and elimination. However, candidate TBV antigens are currently limited, highlighting the urgency of identifying new antigens for TBV development. Methods Using a combination of bioinformatic analysis and functional studies in the rodent malaria modelPlasmodium berghei, we identified a conservedPlasmodium protein PbPH (PBANKA_041720) containing a pleckstrin homology (PH) domain. The expression of PbPH was detected by Western blot and indirect immunofluorescence assay (IFA). The function of PbPH was tested by genetic knockout. The TB activity was confirmed by in vitro ookinete conversion assay and mosquito feeding. Results PbPH was detected in Western blot as highly expressed in sexual stages (gametocytes and ookinetes). IFA revealed localizations of PbPH on the surface of gametes, zygotes, and ookinetes. Deletion of thepbph gene did not affect asexual growth, but significantly reduced the formation of gametocytes, ookinetes, and oocysts, indicating that PbPH protein is required for parasite sexual development. Recombinant PbPH expressed and purified from bacteria elicited strong antibody responses in mice and the antibodies significantly inhibited exflagellation of male gametocytes and formation of ookinetes in a concentration-dependent manner. Mosquito feeding experiments confirmed that mosquitoes fed on mice immunized with PbPH had 13 % reduction in the prevalence of infection and almost 48 % reduction in oocyst density. Conclusions Pbph is a highly conservedPlasmodium gene and is required for parasite sexual development. PbPH protein is expressed on the surface of gametes and ookinetes. Immunization of mice against the recombinant PbPH protein induced strong antibody responses that effectively reduced the formation of male gametes and ookinetes in vitro and blocked transmission of the parasites to mosquitoes. These results highlight PbPH as a potential TBV candidate that is worth future investigations in human malaria parasites.